Mechanosensitive interactions between Jag1 and Myo1c control Jag1 trafficking in endothelial cells - Stassen, Oscar M. J. A.; Virtanen, Noora; Lin, Kai-Lan; Suarez Rodriguez, Freddy; Heijmans, Matthijs J. M.; Zhao, Feihu; Corthals, Garry L.; Bouten, Carlijn V. C.; Sahlgren, Cecilia M. (Cell Press, 2026)
Morphogenesis of the cardiovascular system is responsive to hemodynamic cues sensed by endothelial cells. The organization of morphogenic signaling proteins is regulated by membrane presentation and internalization. Here, we aimed to characterize factors that regulate this flow-dependent protein localization by identifying differential interactors with the Notch ligand Jagged1 in response to shear stress. We cultured endothelial cells expressing Jagged1-APEX2 for proximity labeling on an orbital shaker shear stress platform. Myo1c was identified and confirmed through coimmunoprecipitation as a Jagged1-interacting factor under static conditions, with reduced interaction after exposure to shear. Jagged1 polarization downstream of shear followed by nucleograde transport was inhibited by Myo1c knockout. Further, Myo1c knockdown reduced membrane levels of Jagged1 under static but not shear conditions. Together, our data reveal a role for Myo1c in the hemodynamic control of Jagged1 localization in endothelial cells.